The adversary First Amendment : free expression and the foundations of American democracy - Redish, Martin H. (Stanford, California : Stanford Law Books, an imprint of Stanford University Press, 2013)
This study presents a unique and controversial rethinking of the intersection between modern American democratic theory and free expression. It reshapes free speech as an outgrowth of adversary democracy, arguing that individuals should have the opportunity to affect the outcomes of collective decision-making according to their own personal values and interests. Adversary democracy recognises the inevitability of conflict within a democratic society, as well as the need for regulation of the conflict to prevent the onset of tyranny. In doing so, it embraces pluralism, diversity and individual growth and development.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Freedom of expression -- United States; United States; Democracy -- United States; Politics and Government; United States of America, USA; Politics & government; Human rights, civil rights; Constitutional & administrative law: general